Rancang Bangun Sistem Informasi Pengelolaan Data Pegawai Menggunakan Geolocation Berbasis Website - Ananda Prasta; Zuhri Halim (STMIK Budi Darma, 2023)
The development of information technology has been highly significant, enabling users to access data or information quickly, effectively, and accurately. However, the company's data management system still relies on manual methods, including attendance and payroll systems, leading to administrative inefficiencies and an increased potential for errors in record-keeping and accounting. This research aims to design a web-based information system with geolocation technology, employing a waterfall methodology involving requirements analysis, design, implementation, testing, and maintenance. Developed using the Codeigniter framework, this web application is tailored to the company's specific needs while considering employee requirements. A new paradigm in human resource management encourages the creation of effective web-based solutions for employee payroll and attendance. Geolocation is implemented as a security measure, with a specific radius limitation. The web application development process follows a waterfall methodology, involving requirements analysis, design, implementation, testing, and maintenance. The application is expected to provide an innovative and practical solution for managing payroll and attendance while addressing the needs of employees. Therefore, the designed employee data management information system has successfully achieved its objectives and provides an integrated solution to enhance the employee data management process through the utilization of website-based geolocation.